Alteration of metabolic biomarkers and oxidative stress indices in pashmina (Changthangi) goats under climate change - YATOO, MOHD IQBAL; KANWAR, MAHESHWAR SINGH; WANI, SARFARAZ AHMAD; KUMAR, DINESH; DIMRI, UMESH (The Indian Journal of Animal Sciences, 2016)
The main aim of this study was to evaluate climate change induced variation of metabolic biomarkers and oxidative stress indices in different age groups of pashmina goats. Adult animals in comparison to young and old animals had significantly higher levels of glucose, glycated haemoglobin (GHb), fructosamine and total protein during summer and significantly higher levels of glucose, fructosamine and haemoglobin (Hb) during winter. Significantly reduced levels of these biochemicals were noted in winter than summer in all age groups except for glucose in young and old, GHb in young and Hb in adult animals. Urea and acetoacetate levels were significantly higher in young animals than adults during winter. Higher betahydroxybutyrate and lower propionate levels were noted during winter than summer in all age groups. Significantly higher levels of insulin, T3, T4 and lower levels of TSH and cortisol in adult animals were noted in both seasons. Significant rise of insulin in adult, T3 and T4 in young and old, cortisol in young and TSH in all animals occurred during winter. Level of GSH in summer, CAT and SOD in winter were significantly higher in adult animals whereas, that of LPO were in young animals. Decrease in levels of antioxidants and increase of oxidants during winter was significant in all age groups. Hence, young and old age groups of pashmina goats are more vulnerable to metabolic alterations under climatic stress than the adult group.